2007
DOI: 10.1038/sj.bjp.0707116
|View full text |Cite
|
Sign up to set email alerts
|

Number of nitrate groups determines reactivity and potency of organic nitrates: a proof of concept study in ALDH‐2−/− mice

Abstract: Background and purpose: Mitochondrial aldehyde dehydrogenase (ALDH-2) has been shown to provide a pathway for bioactivation of organic nitrates and to be prone to desensitization in response to highly potent, but not to less potent, nitrates. We therefore sought to support the hypothesis that bioactivation by ALDH-2 critically depends on the number of nitrate groups within the nitrovasodilator. Experimental approach: Nitrates with one (PEMN), two (PEDN; GDN), three (PETriN; glyceryl trinitrate, GTN) and four (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 29 publications
(50 reference statements)
6
67
0
Order By: Relevance
“…PETN was approximately 25-fold less potent on mouse (EC 50 ϭ 0.8 M) than on rat (EC 50 ϭ 0.03 M) aortas. A similar difference in potency of PETN has been reported previously [EC 50 values of 8.5 nM in rat and 170 nM in mouse (Wenzel et al, 2007a) …”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…PETN was approximately 25-fold less potent on mouse (EC 50 ϭ 0.8 M) than on rat (EC 50 ϭ 0.03 M) aortas. A similar difference in potency of PETN has been reported previously [EC 50 values of 8.5 nM in rat and 170 nM in mouse (Wenzel et al, 2007a) …”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have shown that vasorelaxation to PETN is attenuated by pharmacological inhibition or gene deletion of ALDH2 Mollnau et al, 2006;Wenzel et al, 2007a). Although these studies provided circumstantial evidence for a role of ALDH2 in vascular bioactivation of PETN, enzymatic metabolism of the tetranitrate has not been demonstrated so far.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…For instance, we demonstrated that the nitrate pentaerythritol tetranitrate (PETN), although still undergoing mitochondrial activation by the ALDH-2 (Wenzel et al, 2007b), does not induce tolerance and does not stimulate vascular superoxide production in a rat model of nitrate tolerance, two phenomena that probably follow the activation of the antioxidant enzyme heme oxygenase-1 (HO-1) by PETN (Wenzel et al, 2007c). Mitochondrial reactive oxygen species formation was identified as a hallmark of GTN-induced nitrate tolerance (Sydow et al, 2004;Daiber et al, 2005;Esplugues et al, 2006), leading to oxidative ALDH-2 inhibition that could be prevented or reversed in an experimental rat model by (dihydro)lipoic acid (Wenzel et al, 2007a).…”
mentioning
confidence: 99%
“…With the length of the chain being equal, the dinitrooxy-substituted compounds are always more active than the corresponding mononitroxy analogues, in keeping with the statement that the number of nitrate groups determines reactivity and potency of organic nitrates. 46 When the vasodilator experiments were repeated in the presence of 1 µM ODQ, a decrease in the potencies was observed, in keeping with NOinduced activation of the sGS.…”
Section: Chemistrymentioning
confidence: 99%